The Guiding Principles of Police: Use of Force - Thapa, Rabi Raj (Journal of APF Command and Staff College, 2020)
There can be no issue of greater consequence than the use of force for police and law enforcement professionals. In a transitional post-conflict country like Nepal, internal security agencies play a vital role in managing the complexity of political, social and economic transformation. Ever since the end of the feudal oligarchic militaristic Rana regime, internal security and law enforcement took precedence in providing safety and security for the Nepalese people. Since Nepal entered a democratic transition in 1950, it almost failed to consolidate and strengthen its internal security and law enforcement apparatus by appropriately restructuring and consolidating the Nepal Police and National Intelligence functions. Even after the democratic political transformation of 1950, it took five years to establish the national Nepal Police in 1955. Law enforcement agencies are now challenged to solve problems well beyond traditional scope. Therefore, internal security must come up with highly developed methods of policing and law enforcement. Technologically, this may not be possible yet, but it can provide management and training of its personnel based on world standards of policing and emphasizing knowledge and skill enhancement and professional behavior. This paper has tried to focus and analyze the use of force by internal security apparatus of the Government of Nepal in the past and brain-storm its future roles and challenges. The paper is divided into two parts. The first part will touch upon contextual commentary on the use of force in brief. The second part will highlight three time-tested models and procedure of the use of force.